2019
DOI: 10.1016/s2213-8587(19)30061-0
|View full text |Cite
|
Sign up to set email alerts
|

Fully closed-loop insulin delivery in inpatients receiving nutritional support: a two-centre, open-label, randomised controlled trial

Abstract: Summary Background Glucose management is challenging in patients who require nutritional support in hospital. We aimed to assess whether fully closed-loop insulin delivery would improve glycaemic control compared with conventional subcutaneous insulin therapy in inpatients receiving enteral or parenteral nutrition or both. Methods We did a two-centre (UK and Switzerland), open-label, randomised controlled trial in adult inpatients receiving enteral or paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 20 publications
0
75
0
Order By: Relevance
“…We aimed to analyze 15 participants with complete data. The primary endpoint was the percentage of time with plasma glucose between 5.6 to 10.0 mmol/L from 07:00 to 17:00 (10 hours), in line with previous studies in adults with type 2 diabetes using the same fully closed‐loop insulin delivery system . Other endpoints are listed in Table S1.…”
Section: Methodsmentioning
confidence: 92%
“…We aimed to analyze 15 participants with complete data. The primary endpoint was the percentage of time with plasma glucose between 5.6 to 10.0 mmol/L from 07:00 to 17:00 (10 hours), in line with previous studies in adults with type 2 diabetes using the same fully closed‐loop insulin delivery system . Other endpoints are listed in Table S1.…”
Section: Methodsmentioning
confidence: 92%
“…53,54 The use of closed looped systems in inpatients is a technology currently under development and has shown some promising results. 55,56 There are also data to show that education in insulin prescribing reduces insulin errors. 57 Whether electronic records and electronic prescribing will make a difference to the incidence and prevalence of prescribing errors remains to be seen.…”
Section: Technology and Innovation In Diabetesmentioning
confidence: 99%
“…system, and costs of and work needed for integration of these systems into electronic medical records. 11 Another point of concern in this trial 8 is that almost a quarter of patients discontinued the closed-loop system because of discomfort when wearing the device, indicating that future work should focus on the acceptability of wearing these kinds of multifaceted devices and in motivating patients to do the necessary handling, such as finger-sticking, correctly. The positive feedback of participants at the end of the study indicates that closed-loop systems were received positively by most patients.…”
Section: Low-carbohydrate Diets In Type 2 Diabetesmentioning
confidence: 99%
“…In The Lancet Diabetes & Endocrinology, Charlotte Boughton and colleagues 8 report the results of a randomised controlled trial comparing subcutaneous insulin administration via a fully closed-loop system with conventional subcutaneous insulin therapy in accordance with local clinical practice in two centres (in the UK and Switzerland). They showed that, in patients on enteral or parenteral nutrition (or both), an investigational closed-loop system provides superior glycaemic control to conventional therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation